Allergen immunotherapy as add-on to biologic agents. Issue 6 (December 2018) - Lombardi, Carlo; Canonica, Giorgio W.; Passalacqua, Giovanni
Abstract : Purpose of review: In this review, we sought to outline many of the recent evidences about the available clinical trials in which biologic agents [i.e. omalizumab (OMA)] were associated as add-on to allergen-specific immunotherapy (AIT). Recent findings: The available literature shows that OMA may be a valuable option as add-on to AIT for respiratory allergy, or food desensitization, especially in the escalation or build-up phases, in which adverse events are more commonly expected. The encouraging data for hymenoptera venom allergy remain limited to case reports, and no structured clinical trial is available. Summary: Over the past decade, studies of OMA used with AIT have shown promising results. Today, big randomized, double-blind, placebo-controlled trials are needed to better select those patients who would benefit from the addition of OMA (or other biologic agents) to AIT, as well as optimal dosing schedules, optimal duration of treatments and, finally, adequate evaluation about pharmacoeconomic aspects.